Studi Pengembangan Jaringan Saluran Air Desa Gempoltukmloko Kecamatan Sarirejo Kabupaten Lamongan - Supratman, Ach. Ilham Nawadzir; Djaelani, M. Djaelani (Jurnal Basement : Jurnal Teknik Sipil, 2024)
Water is one of the natural resources and a source of life for all living things on earth. No one can deny that water is a very important element for human life. More than just consumption, the need for water supports many human activities on Earth. Gempoltukmloko Village is an area located in Sarirejo District, Lamongan Regency. This scientific work discusses the development of a water channel network which aims to determine the amount of water demand needed and plan development to meet water needs in the Gempoltukmloko Village area, Sarirejo District, Lamongan Regency. This network planning is reviewed from the population growth rate in the study area starting on December 11, 2023 to December 24, 2023, and what is obtained from the results of this study based on the geometric method states that in 2043 the population in the study area reaches 1,201 people and the required discharge is 2,652 lt / d. under these conditions it is necessary to add new pipes at several points with a total length of 718.38 meters. The function of this new pipe installation is because there is no previous network design, this network planning is carried out using the Epanet program method.